Gambaran Cakupan Vaksinasi/Imunisasi Dasar Lengkap - Maulina Apriani; Defvi Nopitasari; Lavina Bella.F.; Imarotun Umamah; Muhammad Angga.P.; Bella Fevi Aristia; Alfu Laila; Eka Putri Nurhidayah; Khoirun Nisak (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2026)
Complete basic immunization (IDL) is a crucial preventive effort to increase children's immunity to various infectious diseases that can be prevented through immunization. In this research review, the literature analysis method was used to select ten journals that had titles and focus of discussion related to the overview of IDL coverage. These journals were identified in the 2015–2025 period through the Google Scholar, Crossref, and Garuda search engines with certain inclusion criteria. The results of the analysis showed that the coverage of IDL in several health facilities in Indonesia was quite high in the initial dose, especially in infants less than one year old. However, the achievement of the follow-up dose is still relatively lower than the first dose. Parents' ignorance about the benefits of immunization, concerns about vaccine side effects, limited access to health services, and delays in visit schedules are the main factors for incomplete immunization. In addition, socioeconomic factors and family support also affect immunization compliance. Therefore, it is necessary to strengthen the role of health workers through continuous education, community-based socialization, and improvement of the immunization recording and monitoring system to ensure the fulfillment of IDL evenly and sustainably.